Komposisi Estetika Dalam Fotografi Ansel Adams - Prasetyo, Martinus Eko; Ika Resmika (IMAGIONARY, 2024)
Photography is the art and practice of capturing images or recording pictures using camera devices to create visual beauty for its audience. One of the most beloved genres of photography is landscape photography, documenting the natural beauty of a place so that it can be retold through visual communication. Ansel Adams is a world-renowned photographer and vocal environmental activist, whose work has become iconic in the world of photography in discussing the importance of preserving the natural beauty of the world. This study aims to explore and analyze the aesthetics of visual composition in Ansel Adams' photographic works. The main focus will be on how Adams utilizes the basic principles of visual composition. Using a qualitative descriptive method approach, this research analyzes Ansel Adams' legendary photographic works, exploring how aesthetics and visual composition can form a language of visual communication in photography for the general audience.